Notes on Bursera heteresthes (Burseraceae) - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2009)
The survey of 135 collections of Bursera heteresthes Bullock, deposited mostly in Mexican herbaria, reveals that: 1.- The known geographic distribution of the species extends from southern Jalisco to eastern Guatemala, but in three separated areas: a) from Jalisco to western Guerrero, b) from eastern Oaxaca to the Central Depression of Chiapas, c) the northern and eastern parts of Guatemala. 2.- In spite of its disjunct distribution and of the remarkable morphological variability of the species, there is no basis to split it into two or more taxonomic entities, and consequently B. steyermarkii Standl., described from Guatemala, is treated as a synonym of B. heteresthes. 3.- The heteromorphic and petaloid staminodes, a character emphasized in the original description of B. heteresthes belongs to a tree with abnormal flowers, and in fact is not characteristic of the species. 4.- The main distinctive characters of B. heteresthes are: a) leaves almost always trifoliolate, seldom with five leaflets and then with a widely winged rachis, b) well developed leaves mostly more than 3 cm long and with a crenate, serrate o dentate margin extending almost to the base, c) inflorescence in the form of rather lax and many-flowered raceme or panicle, with axes usually only bearing glandular pubescence. 5.- although the features of its leaves, inflorescences and flowers approach those of B. biflora (Rose) Standl., B. fragrantissima Bullock and B. infernidialis Guevara & Rzed., its possible phylogenetic relationships are rather towards B. madrigalii Rzed. & Calderón, on account of the widely winged leaf rachis of its quinquefoliolate leaves.An emended description of the species, illustrations showing its known geographic distribution and the variability of its leaf-form, are included, as well as a key to separate the known species of Bursera sect. Bullockia which, at least in some populations, have mainly trifoliolate leaves.